ANALISIS DETERMINAN KEBERHASILAN TURNAROUND PADA PERUSAHAAN YANG MENGALAMI KONDISI FINANCIAL DISTRESS - Nur Wulandari; Barbara Gunawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: This research aims to test the factors that influencing turnaround success of financial distress companies. Sample that used in this research was manufacturing companies that listed on the Indonesian Stock Exchange 2011-2014. Factors that influencing the turnaround success of financial distress companies are company size, profitability ratio, liquidity ratio, severity, assets retrenchments, free assets and growth opportunity. The sample that used on this research are 22 companies for four years period of research, as of that 88 data acquired. Those sample selected using the method of purposive sampling. Test of analysis used logistic regression with SPSS 17.0. Based on the result of research and analysis that has been done, the acquired results of profitability ratio, liquidity ratio and growth opportunity are influence turnaround success of financial distress companies, while the company size, severity, assets retrenchments and free assets are not influence turnaround success of financial distress companies. Keywords: Turnaround, Financial Distress and Logistic Regression